LQR-based nonlinear tuning relay control design with fast convergence - Yu, Xinghuo; Xia, Yang; Ledwich, Gerard; Oghanna, Wardina (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we present a relay control scheme based on LQR design with fast convergence. This scheme provides a practical and simple way to achieve fast convergence based on the well-known LQR design principle. The controller is a global stabiliser in the sense that for any given initial condition, we can always initialize the controller to drive the system to reach the origin.
Keywords: switching control; LQR; relay control; sliding modes